Ukrainian refugees in Germany: escape, arrival and everyday life - Brücker, Herbert; Ette, Andreas; Grabka, Markus M.; Kosyakova, Yuliya; Niehues, Wenke; Rother, Nina; Spieß, C. Katharina; Zinn, Sabine; Bujard, Martin; Cardozo, Adriana R.; Décieux, Jean Philippe; Perleth, Amrei; et al. (IAB-Forschungsbericht, 2023)
The Institute for Employment Research (IAB), the Federal Institute for Population Research (BiB), the Research Centre of the Federal Office for Migration and Refugees, and the Socio-Economic Panel at DIW Berlin have surveyed 11,225 Ukrainian refugees in Germany from August to October 2022. The survey can be extrapolated to the refuge population who has arrived since the beginning of the war at February 24, 2022, to June 8, 2022, in Germany. The results show that the majority of refugees from Ukraine report war as the main flight motive, while personal contacts and respect of human rights were the main reasons to choose Germany as a destination. Roughly 80 percent of adult refugees are women. About the half lives together with minor-aged children, about 80 percent without a partner. Some 70 percent have tertiary education degrees. Yet, only 4 percent report good or very good, another 14 percent fair German language proficiency. About 50 percent visits or has already completed a German language class. 17 percent are employed, with some 70 percent of those performing qualified jobs. The health status of the refugee population is good, but life satisfaction well below the German population average. Above one-third of the refugees plans to stay in Germany forever or for several years, about one-third aim to leave Germany by the end of war, while 27 percent are not yet certain about their staying perspectives.